Public Perception of Social Media as a Platform for Political Campaigns: An Analysis in the Digital Era - Asri, Nadila (Generasi Sains Indonesia, 2024)
In this research, the hypothesis is explored using the perception of people about social media as a campaign system with regard to the efficiency and moral consequences of the targeted advertising. By applying the qualitative methods, the study examines the user reaction towards emotive political advertisements and the effects of emotive political advertisements on political system trust. The results indicate that although targeted advertising serves as an effective way to make the voters interested in the immediate future, it frequently results in long-term disengagement and distrust. The respondents also raised serious concerns regarding any breach of privacy and the control of emotions appeals pointing out that there should be more regulation and transparency in political advertising. The study is relevant to the existing literature because it gives insights into the emotional and ethical aspects of digital political campaigning, the need to encourage actual political participation in the digital age.